Effects of Non-Monetary Rewards on Job Satisfaction of Selected Employees in a Higher Education Institution in Quezon City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study has assessed the effects of non-monetary rewards on the job satisfaction of selected employees in a higher education institution in Quezon City. It aims to determine its significant relationships to their selected profile variables and improve job satisfaction. The researchers used a purposive sampling technique.  The study employed the quantitative research design to collect information about the effects of non-monetary rewards on the job satisfaction of selected employees in a higher education institution in Quezon City. Thirty (30) respondents were selected from selected teaching employees to gather the needed data. A survey questionnaire was also distributed to these respondents.  Based on the result, the teaching staff needs non-monetary rewards. Superiors are recommended to invest in giving employees flowers and cards as a sign of praise. This will encourage the teaching staff to be productive at work and provide extensive training offered to the teachers.
Keywords: non-monetary rewards; job satisfaction; employees; higher education institution